Between Exu and Ogum: politics of the sacred in the drama by Abdias do Nascimento - Lima, Rainério dos Santos (2020)
Critical study of mythic determinants in the construction of characters and composition of action in Sortilégio II (“Sortilege II”), drama by Abdias do Nascimento. The theater by Abdias obeys to paradigms of scene composition that go beyond the sintagmatic organicity of fable, but, in presenting the complexes and passions of Emanuel, it searches a discontinuous and paradigmatic organization in order to deal with the life of a unique and dominant subjectivity in scene. In Sortilégio II, this post-catastrophe theater configuration is ideal to weave the Emanuel’s rememorative processes in the attempt to project the character traumatic past onto the present scene, marked by social violence, racial complexes and contradictory erotic relations with Ifigênia and Margarida. In the play, besides the structural definitions of action, the Afro-Brazilian sacred and the Orishas mythology are important cultural modulations that interfere in the relations of power among agents and in the processes of subjectivation that affect Emanuel. A social and symbolic network, under the tutelage of Eshu and Ogoun, contributes to the liberation and deification of the character. Through the recognition of black culture, of ethno-racial belonging, and mythical sacrifice, Emanuel leaves the human racist world to inhabit Orún, the divine plan of the Orishas.